Food Supplementary Consumption of Females in Mueang District, Nakhon Ratchasima Province - Singtipphun, Chalermsri (Journal of Health Science of Thailand, 2018)
Supplementary diet for health is very popular, especially among women. These type of product markets have grown rapidly, even during the economic crisis. Manufacturers had to adjust strategy to capture market share. This study was descriptive cross-sectional research which was aimed at studying the factors of attitudes and dietary habits to enhance women’s health in the urban of Nakhon Ratchasima province by using simple random sampling netting 400 samples. During February-September 2007, questionnaires were used to collect survey data. They comprised of 4 parts: general information, attitude, influence of individual differences and behavioral information. The data were analyzed by employing descriptive statistics and chi-square test to compare attitude, buying behavior and consumption related to supplementary diet with factors on clients and purchasing decision. It was found that most samples knew dietary supplement products and bought them for their own consumptions. Decisions on the consumptions were based on peers and television advertisements. Their attitudes were significantly affected by age, and levels of education (p < 0.05). On the contrary, behaviors on consumption of food supplement were not related to age, occupations and levels of education (p > 0.05). While actual consumptions were related to age and occupations. It was recommended that the information should be applied to strategy development on nutrition and health promotion services for the public. Focus should be made on strategy and public relations planning to disseminate information on well balanced diets targeting women in Mueang district, Nakhon Ratchasima province.